ANALYSIS OF CRIMINAL ACTIONS THROUGH TERRORISM FUNDING CHARITY BOX MONEY REVIEWED BY LAW NUMBER 9 OF 2013 CONCERNING PREVENTION AND ERADICATION OF CRIMINAL ACTS TERRORISM FUNDING - Sitompul, Siti Nur Chadijah (Inspiring Law Journal, 2024)
Criminal acts of terrorism are acts that involve elements of violence or cause dangerous effects on human life that violate the criminal law. The criminal act of financing terrorism in Indonesia is an integral part of the criminal act of terrorism. This is because the criminal act of financing terrorism is regulated simultaneously with the criminal act of terrorism in Government Regulation in Lieu of Law Number 1 of 2002 concerning the Eradication of Criminal Acts of Terrorism as amended into Law based on Law No. 15 of 2003. Normative Juridical Research Method, with a statutory approach, which is descriptive analytical in nature. Data collection techniques and tools were carried out using literature studies and field studies. Data sources are primary data and secondary data with qualitative data analysis. The mode of financing terrorism through foundations is dominant and has the potential for high risk because the source of the funds generally comes from legal activities, for example donations/contributions from the community from work. other factors that motivate someone to join a terrorist network. This motivation is caused by several factors. First, domestic factors, namely domestic conditions such as poverty, injustice or feeling disappointed with the government. Second, international factors, namely the influence of the foreign environment which provides the impetus for the growth of religious sentiments such as global injustice, arrogant foreign policy, and modern imperialism of superpower countries. Third, cultural factors are closely related to shallow religious understanding and narrow and lexical (literal) interpretation of holy books. three factors that encourage the emergence of a soft approach. Legal responsibility is interpreted as an obligation to carry out certain things or conduct behavior based on certain methods that do not violate previously existing rules. Legal responsibility can also be defined as the consequences of a criminal event that the legal subject commits, in this way criminal responsibility for the perpetrator of the funding for terrorist activities is to carry out the role of the consequences of the criminal act that the legal subject commits, which means that the consequences of his actions are in line with the rules. existing and applicable laws in the State of Indonesia